Efektivitas Pendidikan Kesehatan dengan pendekatan Modelling terhadap Pengetahuan dan Sikap Ibu Nifas Tentang Teknik Menyusui di Kelurahan Panggungjati Wilayah Kerja UPTD Puskemas Taktakan - Annisa Nurhayati Hidayat; Putri Ajeng Anggraeni; Susi Irianti (Inovasi Kesehatan Global, 2024)
Breastfeeding technique is a factor that affects milk production, wrong breastfeeding technique will cause problems in breastfeeding such as sore nipples, less milk production. This is caused by a lack of knowledge and attitudes of mothers about proper breastfeeding techniques. To increase the knowledge and attitudes of mothers, it is necessary to provide health education about breastfeeding techniques using a modeling approach. The purpose of this study was to analyze the effectiveness of health education with a modeling approach to the knowledge and attitudes of postpartum mothers regarding breastfeeding techniques. The research design is a Quasi-Experimental Pre-Test-Post-Test. The sample in this study were 30 nursing mothers aged 0-6 months using the Total Sampling technique. Data were analyzed using the Wilcoxon test. The results of the study obtained a p value of 0.000 so that the modeling approach was effective in increasing the knowledge and attitudes of postpartum mothers regarding breastfeeding techniques. The conclusion of this study is the effectiveness of health education with a modeling approach to increasing the knowledge and attitudes of postpartum mothers regarding breastfeeding techniques in Panggungjati Village.